(untitled) (Journal of Geography and Environmental Management, 2022)
The rapid development of irrigated agriculture in the Aral Sea basin led to two main consequences that had a significant impact on the quality of river waters: a decrease in fresh water reserves and an increase in pollutants along with wastewater, the main of which are various toxic salts. As a result, wastewater from irrigated lands, contaminated with various agrochemical wastes, mixes with river water, deteriorating the quality of the remaining water resources in the river. In addition to the agricultural sector, which is polluted with salts and agrochemical waste, it is worth noting the pollution of the industrial and domestic sectors with harmful substances from large areas. Water quality in the Syrdarya River in Kazakhstan is affected by pollutants from Uzbekistan. Water polluted with nitrites and phenols with an average annual concentration of 4 MPC (maximum permissible concentration) is discharged into river water at a site near the village of Kokbulak (frontier post), and its iron and oil products reach up to 1 MPC. Most of the analyzed samples have higher levels of nitrite, but high levels of contamination are not usually observed. Significant pesticide pollution is observed during the growing season. In the lower part of the Shardara reservoir, the level of pesticides in the water is significantly reduced, while the concentration of other pollutants remains high. The level of pesticide pollution in the lower reaches of the river increases and reaches its peak in the area of ​​the modern (Kazalinsky) delta. In this part of the river, among other pollutants, there is a systematic increase in the concentration of oil products, nitrite nitrogen and organic matter. The impact of irrigated agriculture on the natural and ecological situation in the irrigated territories of Kazakhstan is determined by the Concept for the Development of Agriculture in Central Asia and Kazakhstan. The issue of stabilizing the ecological situation in the irrigated territories of Kazakhstan, restoring the ecological and reclamation situation is directly related to various water management regions of Kyrgyzstan and Uzbekistan. The article deals with the issues of determining the damage caused by pollution of the Syrdarya River and assessing the amount of damage from pollution.